Metode arhivskega strokovnega dela na področju digitizacije gradiva Pokrajinskega arhiva Maribor - Valadžija, Špela (Moderna arhivistika, 2023)
The purpose of this paper is to present the methods of archival professional work in the field of digitization of archival records and to describe the process of converting material from physical to digital form based on a review of guidelines and considering international standards. Accessible technology enables digitization to be carried out within an organization with available resources, equipment and personnel. The aim of the paper is to present challenges and solutions, from the preparation of materials to publication in the Virtual Archival Reading Room, with an emphasis on the recent digitization of information aids from the fond Administration for Construction and Regulation Maribor, which was carried out by archival workers with the existing equipment of the institute. At the same time, the construction plans of the mentioned and extensive fond are also systematically digitized by an external service provider.
Keywords: archival records; arhivsko gradivo; building plans; gradbeni načrti; internal digitization; notranja digitizacija; uporaba digitizatov; use of digitizers; Virtual Archival Reading Room; Virtualna arhivska čitalnica